Mental Health Program Implementation of Local Universities and Colleges (LUCs) in Zambales: Basis for Action Plan Development - Ebro, Eric DS.; Mantillas, Christopher C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The local universities and colleges (LUCs) in the Philippines crafted local policies and developed programs on mental health to prioritize the well-being of workers in accordance with the provisions of RA 11036, otherwise known as the Mental Health Act, and CSC MC 4 s. 2020, otherwise known as the Mental Health Program in the Public Sector. The study aimed to describe the extent of implementation of mental health programs (MHPs) in LUCs and explore the program implementation experiences. Using a mixed-method research design, the data were gathered through surveys among 49 school managers selected through proportional stratified random sampling from three LUCs in the province of Zambales. Results from the rating scale items indicate that the mental health programs are implemented in terms of Management, Technical Package, Partnerships, and Communication components. Moreover, the experiences of the management highlighted the themes of beneficial opportunities, management of feelings and behaviors, and engagement in appropriate programs and activities, as well as lack of budget and limited relevant programs and activities. The Action Plan serves as the study's output, addressing the areas needing improvement through doable interventions.